Sleep status of older adults with sleep apnoea syndrome may vary by body mass index - Tanaka, Yuji; Baba-Mori, Naana; Yonaga, Takaaki; Mochizuki, Kazuki; Igarashi, Satoshi; Ando, Takashi; Kohda, Takashi; Ito, Yasumi; Soejima, Kenzo; Sakurai, Daiju (Frontiers in Aging, 2024)
Obesity and ageing are the most important risk factors for sleep apnoea syndrome (SAS); however, the role of body mass index (BMI) on sleep status in healthy older adults is unclear. To explore sleep parameters according to BMI among active older adults, we cross-sectionally examined the relationship between sleep-related parameters and BMI in 32 Japanese adults aged from 83-95 years without long-term care who were unaware of having SAS. Correlation and linear regression analyses were performed. Moderate or severe SAS prevalence was high in both those with low (68.8%) and high (68.8%) BMI. A higher increase in apnoea-hypopnoea index (AHI) was negatively correlated with sleep depth in the high-BMI group. In the low-BMI group, the number of awakenings and age were positively correlated with AHI. Older adults may have SAS regardless of their BMI, and the sleep status of patients with SAS may vary by BMI.